Trophic State of The Perupuk Lake in Kampung Pinang Kampar Regency Riau Province Based on Nygard Index - Simanjuntak, Taruli Septiana; H Simarmata, Asmika; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Nygard Index can be used to determine the trophic state of waters. Calculation of this index is based on the number of phytoplankton species that are belonged to these following groups, namely  Chlorococcales, Myxophyceae, Centric diatom, Euglenophyceae, and Desmidiaceae. To understand the trophic state of the Perupuk Lake, a research has been conducted in June-July 2019. There were three sampling stations, namely station 1 (in the inlet from the Kampar River), station 2 (in the middle of the lake) and station 3 (in the end of the lake). In each station there were two sampling points, in the surface and in the middle of water column. Sampling were conducted 3 times, once/week. Water quality parameters measured were phytoplankton type, transparency, temperature, pH, nitrate, phosphate, dissolved oxygen and free carbon dioxide. Results shown there were 18 species of phytoplankton present, namely Chlorococcales order (5 species), Myxophyceae (4 species), Centric diatom order (3 species), Euglenophyta Division (1 species) and Desmidiaceae (5 species). Water quality parameters were as follows: transparency 44.3-49.3 cm, temperature 28.3-300 C, pH 5, nitrate 0.11-0.17 mg/L, phosphate 0.02-0.04 mg/L, dissolve oxygen 5.07-6.40 mg/L, and  free carbon dioxide 7.3-14.6 mg/L. Nygaard Index value of the Perupuk Lake range 1.75-2.5 and it can be  categorized as mesotrophic.Keywords: Trophic State of lake, phytoplankton, mesotrophic, water quality.